2017
DOI: 10.1186/s12284-017-0170-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Expression Analysis of Rice and Arabidopsis Peroxiredoxin Genes Suggests Conserved or Diversified Roles Between the Two Species and Leads to the Identification of Tandemly Duplicated Rice Peroxiredoxin Genes Differentially Expressed in Seeds

Abstract: BackgroundPeroxiredoxins (PRXs) have recently been identified as plant antioxidants. Completion of various genome sequencing projects has provided genome-wide information about PRX genes in major plant species. Two of these -- Oryza sativa (rice) and Arabidopsis -- each have 10 PRX members. Although significant progress has been made in understanding their biological roles in Arabidopsis, those functions in rice, a model crop plant, have not been well studied.ResultsWe performed a comparative expression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
0
9
1
Order By: Relevance
“…S11 D and S12 ). The rice genome contains 10 members of the PRX genes with diversified spatiotemporal expression patterns, and one of which, PER1A (also called Os1-CysPrxA ), was preferentially expressed in the seeds ( 36 ). We also observed that PER1A was expressed far more pronounced than the other four identified DE members, with its allelic transcript level of Kasalath stronger than that of Jigeng88 ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S11 D and S12 ). The rice genome contains 10 members of the PRX genes with diversified spatiotemporal expression patterns, and one of which, PER1A (also called Os1-CysPrxA ), was preferentially expressed in the seeds ( 36 ). We also observed that PER1A was expressed far more pronounced than the other four identified DE members, with its allelic transcript level of Kasalath stronger than that of Jigeng88 ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The tandemly duplicated PRX genes in rice, Os1-CysPrxA and Os1-CysPrxB, also have different expression patterns. Although tandemly duplicated PRX genes in rice, Os1-CysPrxA and Os1-CysPrxB, might be functionally redundant due to high amino acid sequence similarity, their anatomical expression patterns are quite different (Gho et al, 2017). It has been reported that their promoters contain unique tissuepreferred CREs: the promoter of Os1-CysPrxA has CREs for endosperm preferred expression, while that of Os1-CysPrxB has embryo or root-preferred CREs.…”
Section: Discussionmentioning
confidence: 99%
“…This case demonstrates that a phylogenetic heatmap is useful even in the case of partial or unequal functional redundancy because researchers are still able to check the degree of functional redundancy using three different colored boxes (yellow, orange, and red). Moreover, it can be used to identify cis ‐acting regulatory elements between two closest genes having different expression patterns, as in the research about the rice peroxiredoxin family (Gho et al ., 2017; Figure S2b).…”
Section: Resultsmentioning
confidence: 99%